Medication safety in intravenous therapy: A compatibility study of clonidine with drugs frequently used in intensive care - Koller, Anna Katharina; Krebs, Sabine; Dörje, Frank (Pharmaceutics, 2021)
The intravenous pharmacotherapy of critically ill patients is extremely challenging due to the high number of drugs administered. We therefore evaluated the physicochemical compatibility of combinations of clonidine with drugs frequently used in an intensive care unit setting. Amiodarone, dihydralazine, furosemide, levosimendan, metamizole, milrinone, urapidil, and verapamil were each prepared as binary combinations with clonidine at the standard low and high administration concentrations. Selected ternary combinations were also analyzed. Samples were examined for physical compatibility. To verify chemical compatibility in samples deemed either physically compatible or to exhibit uncertain results, the drug content was quantified using high-performance liquid chromatography. Admixtures of clonidine with amiodarone or furosemide proved to be physically incompatible, whereas mixtures with levosimendan and metamizole exhibited results, which were not clearly meeting the specification criteria for physical compatibility. Binary combinations of clonidine with dihydralazine, milrinone, urapidil, and verapamil were found to be physically compatible. Combinations with dihydralazine, levosimendan, metamizole, milrinon, urapidil, or verapamil were chemically compatible for the analyzed concentrations. Ternary admixtures of clonidine, metamizole, and urapidil; clonidine, metamizole, and verapamil; clonidine, urapidil, and verapamil were shown to be physicochemically compatible for the analyzed concentrations. These data suggest that clonidine can be coadministered with dihydralazine, levosimendan, metamizole, milrinone, urapidil, and verapamil. However, the concomitant administration of clonidine with amiodarone or furosemide is not recommended.
CRIS-Team Scopus Importer:2021-01-29
Keywords: Clonidine hydrochloride; Incompatibility; Infusion therapy; Medication safety; Precipitation; Y-site compatibility